Behavior and body surface temperature of beef cattle in integrated crop-livestock systems with or without tree shading - Giro, Alessandro; Macedo Pezzopane, Jose Ricardo; Barioni Junior, Waldomiro; Pedroso, Andre de Faria; Lemes, Amanda Prudencio [UNESP]; Botta, Daniela; Romanello, Narian; Barreto, Andre do Nascimento; Garcia, Alexandre Rossetto (Elsevier B.V., 2019)
Pasture-based livestock production is largely centered on monoculture systems that degrade grasslands. In integrated crop-livestock-forestry systems a synergy is supposed to occur between its components, contributing to global food production. Thus, this study aimed to evaluate the effects of the microclimate on integrated crop-livestock-forestry (CLF) and crop-livestock (CL) systems on the behavior and body surface temperatures of beef cattle in a tropical climate. The experiment was carried from December/2016 to June/2017. Adult beef cows were maintained in CL (n = 11) or CLF (n = 12) systems, permanently monitored by automatic weather stations. The microdimatic conditions indicated that CLF was more effective in mitigating the environmental heat load. Animals maintained in CLF showed favorable behavior, longer rumination (42.9 +/- 2.2 vs 36.6 +/- 22 min) and shorter resting time (57.6 +/- 2.7 vs 65.9 +/- 2.8 min) during the morning. The grazing time and other activities did not differ between treatments (P> 0.05) in the afternoon. Animals in CLF exhibited lower surface temperatures of the back (TBack: 31.9 +/- 02 vs 32.8 +/- 02 degrees C, P < 0.05) and of the trunk (TTrunk: 32.0 +/- 0.1 vs 32.5 +/- 0.1 degrees C, P < 0.05) measured by infrared thermography. Animals maintained in CLF showed a significant preferential use of shade and a 23% reduction in the frequency of the animals searching for water troughs. It is evident from the study that integrated crop-livestock-forestry systems can be used to provide a more favorable microclimate within grasslands. Thus, beef cattle benefits from the milder environment and exhibits a higher thermal comfort, which favors food production and the rational use of natural resources. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Bovine; Food production; Shadow; Silvopastoral system; Thermal comfort; Infrared thennography